TURKEY EFFORTS BECOME PERMANENT MEMBER IN THE SHANGHAI COOPERATION ORGANIZATION (SCO) - Lidia Lorenta Sitorus; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research review Turkey eforts become permanent member of the shanghai cooperation organization (SCO) Turkey's interests colected with shanghai cooperationor ganization (SCO) began in 2011. First colected of Turkey in SCO becomingTurkey decided as partners dialogue in the SCO in 2011. Turkey has interests in the SCO in Military and economic. For the limited Turkey role in the SCO becoming Turkey is efforting to increase status of Tukey become permanent member of the SCO, in the prime minister of Recep Tayyib Erdogan. Colected in the SCO is one of startegic Politic Turkey that include military and economic. After selected President Edorgan as head of the Turkey Goverment, trend of Turkey foreign politic begin to the Asia. Add with obscurity status of Turkey in The Europe union to motivate Edorgan for choosing to colected as member of the Shanghai cooperation Organization. This research has theoretically been build using the neorealis perspective, this type of research is qualitative research. Data prsesented on secondary data through literature studies such as books, internet and other.The result of this reseach is Turkey efrots become permanent member in the SCO by doing negotiation and participate in the SCO. Turkey to submit an application for membership became obeserver state in 2013. In Conferensi pers in st.petersburg, prime minister Edorgan to ask president Vladimir Putin to enter Turkey as legitimate member SCO. Then, Turkey has showed their work with bilateral relation and collaboration with the state of member SCO. In security, Turkey has taken part of practice anti teror, Kasygurt antiteror 2013 was implemented in Kazakhstan. In Economic Turkey has taken part energy club and Turkey has selected as head of energy club. and Turkey follow take part in meeting in SCO.Keyword : Shanghai Cooperation Organization ,Turkey, Military, Economic